Analisis Strategi Penjualan Produk Digital di Shopee: Studi Observasi dan Eksperimen pada Toko Pribadi: Penelitian - Milton Siahaan; Saut Dohot Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesian e-commerce has grown rapidly over the past five years, particularly for digital products due to easy access and flexibility. This study analyzes digital product sales strategies on Shopee through observations of ten stores (March–July 2025) and experiments at the researcher's store. The main focus includes pricing strategies, platform promotions, visual optimization, upload times, and reputation management through reviews and customer interactions. Results show that initial competitive pricing strategies, attractive visuals, and content consistency increase visibility and sales. A store's reputation with positive reviews significantly impacts consumer trust and sales sustainability. Experiments demonstrate that penetration pricing effectively accelerates positive reviews and initial loyalty, resulting in stable sales even when prices are raised. Research barriers include limited access to competitor data and research time management. The study recommends a reputation-based strategy and competitive initial pricing as the foundation for the long-term success of digital products in e-commerce.